Effect of glutathione foliar spraying and hydrogen peroxide seed soaking on some growth traits of mung bean Vigna radiata L. (Journal of the College of Basic Education, 2022)
Two field experiments were conducted during the growing season of the spring and autumn vines of Vigna radiata L. for the year 2014 in the botanical garden of the Department of Life Sciences / College of Education for Pure Sciences (Ibn Al-Haytham) / University of Baghdad, with the aim of studying the effect of foliar spraying with glutathione at a concentration of 0, 25, 50 100, 75 mg.l-1 and soaking the seeds with hydrogen peroxide H2O2 at concentrations of 0, 5, 10, 15 mmol.l-1 in some characteristics of vegetative growth of mung bean plant, the results showed an increase in plant height at a concentration of 100 mg.l-1 With a percentage of 23.71% and 37.14% for the first and second loops, and for a concentration of 10 mmol.l-1 of hydrogen peroxide, with an increase of 8.58% and 18.88%, and in the diameter of the stem with the same concentration of glutathione, an increase of 34.56% and 28.00% for both loops, respectively. Stem diameter increased in 15 mmol .L-1 concentration of hydrogen peroxide